Marketing - Grewal, Dhruv (McGraw-Hill Education, 2016)
Grewal/Levy's Marketing was designed for today’s social, mobile and digital student population, with an emphasis on how firms analyze, create, deliver, communicate, and capture value. Underscoring that even the best products and services will go unsold if marketers cannot communicate their value, Marketing explores both fundamentals and new marketing influencers and features comprehensive coverage, topics like social media and ethics integrated throughout, a robust suite of instructor resources, and regularly updated Grewal/Levy author blog with content tagged by chapter to help keep your classroom discussions current, fresh and engaging